Spatially resolved monitoring of crystalline suprastructure and molecular orientation in α‐ and β‐nucleated polypropylene pipes using differential scanning calorimetry, infrared microscopy, and polarized light microscopy. Issue 6 (13th July 2013) - Schuster, Tobias; Rode, Karsten; Brüll, Robert; Heinemann, Jürgen; Haupt, Hansgeorg
ABSTRACT Differently nucleated polypropylene (PP) pipes were studied by polarized light and infrared (IR) microscopy and differential scanning calorimetry (DSC). Although Fourier transform IR microscopy (µFTIR) excels by high spatial resolution and ease of measurement over the classical approach with manually prepared sections and individual analysis, a disadvantage is that the vibrational bands used to calculate the degree of crystallinity may be influenced by the polymorphism of PP. While this does not play a role for the α‐polymorph, in the case of β‐nucleated PP the calculated profile of crystallinity derived from the so called crystallinity bands depends on the direction of inspection. We could show that in the case of β‐nucleation the results from µFTIR and DSC of cross‐sections can be correlated, and thus the crystallinity profile obtained from µFTIR becomes independent from the direction of consideration. Consequently the advantages of µFTIR with regard to spatial resolution and reproducibility can now be exploited for β‐nucleated PP as well. Using the differently nucleated specimen we give the first practical validation of a previously on a theoretical basis derived model to determine the molecular orientation in all three dimensions (machine, transverse, and normal). It could be shown that the profiles of molecular orientation are a function of both, the extrusion process with its post extrusion cooling conditions, and the type of nucleating agent. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4182–4190, 2013